Web services-oriented architectures for mobile SOLAP applications. (18th August 2008) - Badard, Thierry; Bedard, Yvan; Hubert, Frederic; Bernier, Eveline; , Etienne Dube
With the growing popularity of mobile computing and the empowerment of mobile devices by high end-users and decision-makers, the development of architectures based on web services for the deployment of mobile Spatial OLAP (SOLAP) applications is being perceived as a powerful solution. This paper deals with geospatial (web) Services-Oriented Architectures (SOA) for mobile processing of geo-decisional information. The paper first reviews the underlying concepts of typical SOLAP applications as well as the general concepts of mobile computing. The existing SOLAP functionalities are presented and their viability/usefulness in a mobile environment are discussed. Different web services based on an extended geospatial SOA are then proposed in order to tackle the several issues related to mobile SOLAP. Finally, several research challenges and outlooks are discussed.